2008
DOI: 10.1111/j.1365-2958.2008.06492.x
|View full text |Cite
|
Sign up to set email alerts
|

The ribosomal stalk is required for ribosome binding, depurination of the rRNA and cytotoxicity of ricin A chain in Saccharomyces cerevisiae

Abstract: SummaryRibosome inactivating proteins (RIPs) like ricin, pokeweed antiviral protein (PAP) and Shiga-like toxins 1 and 2 (Stx1 and Stx2) share the same substrate, the a-sarcin/ricin loop, but differ in their specificities towards prokaryotic and eukaryotic ribosomes. Ricin depurinates the eukaryotic ribosomes more efficiently than the prokaryotic ribosomes, while PAP can depurinate both types of ribosomes. Accumulating evidence suggests that different docking sites on the ribosome might be used by different RIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(132 citation statements)
references
References 53 publications
0
131
1
Order By: Relevance
“…It was observed that although the K m values of RTA for the rat ribosome and naked 28S rRNA were similar, RTA exhibited 10 5 -fold higher catalytic activity (K cat ) on the rat ribosome than on naked 28S rRNA (31). A subsequent study revealed that RTA could interact with the C-terminal region of the ribosomal P stalk proteins (P0, P1, and P2), and yeast ribosome with the P stalk protein mutants were depurinated less than the wild-type ribosomes (32,33). To examine whether 6C2 interfered with the interaction between RTA and ribosome, and thus inhibited the activities of RTA, we performed an SPR experiment.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that although the K m values of RTA for the rat ribosome and naked 28S rRNA were similar, RTA exhibited 10 5 -fold higher catalytic activity (K cat ) on the rat ribosome than on naked 28S rRNA (31). A subsequent study revealed that RTA could interact with the C-terminal region of the ribosomal P stalk proteins (P0, P1, and P2), and yeast ribosome with the P stalk protein mutants were depurinated less than the wild-type ribosomes (32,33). To examine whether 6C2 interfered with the interaction between RTA and ribosome, and thus inhibited the activities of RTA, we performed an SPR experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The increased activity of RTA/PAP-S1 compared to PAP-S1 alone can probably be explained by the fact that PAP-S1 and RTA do not dock onto the ribosome at the same site. Indeed, it was found that after PAP-S1 partially depurinates the E. coli ribosome, RTA is able to depurinate the same ribosome while RTA cannot depurinate an intact E. coli ribosome on its own [19][20][21][22][23][24][25][26]. …”
Section: Inhibitory Activity Of Recombinant Proteins On E Coli Protementioning
confidence: 99%
“…Monomeric ribosomes were isolated from yeast cells as previously described (Chiou et al 2008). Ribosome depurination was performed as previously described (Chiou et al 2008) using 10 mM Tris pH 7.4, 10 mM MgCl 2 , 60 mM KCl, 2 mM DTT, ricin A chain (Vector Laboratories), and 10 pmol purified yeast ribosomes at 30°C in 100 mL.…”
Section: Treatment Of Ribosomes With Rta and Shiga Toxinmentioning
confidence: 99%
“…Ribosome depurination was performed as previously described (Chiou et al 2008) using 10 mM Tris pH 7.4, 10 mM MgCl 2 , 60 mM KCl, 2 mM DTT, ricin A chain (Vector Laboratories), and 10 pmol purified yeast ribosomes at 30°C in 100 mL. The reaction was stopped by the addition of 100 mL 23 extraction buffer (240 mM NaCl, 50 mM Tris-HCl pH 8.8, 20 mM EDTA, 2% SDS) and RNA was isolated by phenol extraction as described for the primer extension assay (Parikh et al 2002).…”
Section: Treatment Of Ribosomes With Rta and Shiga Toxinmentioning
confidence: 99%
See 1 more Smart Citation